2021
DOI: 10.1007/s00018-021-04040-0
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and Rho GTPases in the biogenesis of tunnelling nanotubes: implications in disease and therapy

Abstract: Tunnelling nanotubes (TNTs) are an emerging route of long-range intercellular communication that mediate cell-to-cell exchange of cargo and organelles and contribute to maintaining cellular homeostasis by balancing diverse cellular stresses. Besides their role in intercellular communication, TNTs are implicated in several ways in health and disease. Transfer of pathogenic molecules or structures via TNTs can promote the progression of neurodegenerative diseases, cancer malignancy, and the spread of viral infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 137 publications
(155 reference statements)
0
17
0
Order By: Relevance
“…Namazi et al used the transverse isotropic constitutive relation to simulate the local deformation behavior of geomaterials in triaxial symmetric compression test, which considered the case of shear zone and pure compression zone [5]. Raghavan et al established an elastic-plastic damage model of geological materials under the framework of continuous thermodynamics, the tensile stress damage is considered in the model, the plastic potential function is based on the Drucker-Prager criterion, and the damage is a function of volumetric strain [6]. Anirban has conducted a lot of systematic research on the elastic-plastic damage constitutive model of rock materials; considering the hydraulic properties of rock under saturated and unsaturated states, an elastic-plastic damage coupled constitutive model of semibrittle materials is established and compared with the experimental results [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Namazi et al used the transverse isotropic constitutive relation to simulate the local deformation behavior of geomaterials in triaxial symmetric compression test, which considered the case of shear zone and pure compression zone [5]. Raghavan et al established an elastic-plastic damage model of geological materials under the framework of continuous thermodynamics, the tensile stress damage is considered in the model, the plastic potential function is based on the Drucker-Prager criterion, and the damage is a function of volumetric strain [6]. Anirban has conducted a lot of systematic research on the elastic-plastic damage constitutive model of rock materials; considering the hydraulic properties of rock under saturated and unsaturated states, an elastic-plastic damage coupled constitutive model of semibrittle materials is established and compared with the experimental results [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though expression of both proteins Miro1 and Miro2 was found elevated in different types of patient tumors, crucial in vitro and in vivo data showing direct involvement of these proteins in the process of horizontal mitochondrial transfer in cancer are still missing. Available data we have are of an indirect character via involvement of Miro in the mitochondrial transport in TNTs (Qin et al, 2021;Raghavan et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
“…Essential role of Miro in intercellular transfer of mitochondria has been demonstrated by many studies reporting a correlation between Miro expression and mitochondria exchange with TNTs being the conduits for the transport ( Ahmad et al, 2014 ; Babenko et al, 2018 ; English et al, 2020 ; Tseng et al, 2021 ; Wang et al, 2021 ). Except for one study, presence of Miro was found essential for the transfer/movement of mitochondria along TNTs rather than for their formation ( Babenko et al, 2018 ; Raghavan et al, 2021 ). Although direct evidence connecting Miro to a particular alteration in TNT’s dynamic or structure is still missing, the process of TNTs formation via cytoskeleton and membrane remodeling is energetically demanding, with positioning of mitochondria (involving Miro) likely playing a role.…”
Section: Tunneling Nanotubesmentioning
confidence: 94%
See 2 more Smart Citations